1998
DOI: 10.1523/jneurosci.18-21-09078.1998
|View full text |Cite
|
Sign up to set email alerts
|

Light Responsiveness of the Suprachiasmatic Nucleus: Long-Term Multiunit and Single-Unit Recordings in Freely Moving Rats

Abstract: The suprachiasmatic nuclei (SCN) of the hypothalamus contain a pacemaker that generates circadian rhythms in many functions. Light is the most important stimulus that synchronizes the circadian pacemaker to the environmental cycle. In this paper we have characterized the baseline neuronal firing patterns of the SCN as well as their response to light in freely moving rats. Multiunit and single-unit recordings showed that SCN neurons increase discharge during daytime and decrease discharge at night. Discharge le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
162
2
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(180 citation statements)
references
References 43 publications
15
162
2
1
Order By: Relevance
“…Thus the GABAergic network may behave as an active filter that passes excitatory inputs during the night but cuts them off during the day. This idea is in line with the enhanced light-responsiveness of SCN neurons at night compared with day (Meijer et al 1998). Propagation of light information throughout the SCN was also indicated by spatiotemporal SCN profiles of clock gene expression (e.g., mper1) and activity markers (e.g., c-fos) (Albrecht et al 1997).…”
Section: Discussionsupporting
confidence: 70%
“…Thus the GABAergic network may behave as an active filter that passes excitatory inputs during the night but cuts them off during the day. This idea is in line with the enhanced light-responsiveness of SCN neurons at night compared with day (Meijer et al 1998). Propagation of light information throughout the SCN was also indicated by spatiotemporal SCN profiles of clock gene expression (e.g., mper1) and activity markers (e.g., c-fos) (Albrecht et al 1997).…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies have shown rat SCN neurons to be more active during the subjective day, when animals are predominantly asleep (Meijer et al, 1997(Meijer et al, , 1998Deboer et al, 2003) and when the sleep-promoting VLPO neurons would also be most active (Sherin et al, 1996). This profile of SCN activity in relation to VLPO activity appears to contradict our results, because we show that increased activity in SCN neurons produces an inhibition of VLPO sleep-promoting neurons.…”
Section: Discussioncontrasting
confidence: 99%
“…1C). In keeping with this strong light trigger of the rodent endogenous circadian clock (Pittendrigh and Daan, 1976;Meijer et al, 1998), the period of vigilance was followed by a period of drowsiness (Fig. 1C).…”
Section: Diurnal Changes In Illuminance Generate Fluctuations In Basamentioning
confidence: 61%